2010
DOI: 10.1016/j.stem.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Oct4 Interaction Network: Implications for Stem Cell Biology, Development, and Disease

Abstract: SummaryThe transcription factor Oct4 is key in embryonic stem cell identity and reprogramming. Insight into its partners should illuminate how the pluripotent state is established and regulated. Here, we identify a considerably expanded set of Oct4-binding proteins in mouse embryonic stem cells. We find that Oct4 associates with a varied set of proteins including regulators of gene expression and modulators of Oct4 function. Half of its partners are transcriptionally regulated by Oct4 itself or other stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
379
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(413 citation statements)
references
References 78 publications
24
379
4
2
Order By: Relevance
“…Additionally, it has been suggested that b-catenin can interact with ES cell regulator Oct4 and in turn up-regulate Oct4 target genes ( Fig. 3E; Pardo et al 2010;van den Berg et al 2010). These interactions seem to be dependent on the stabilization of b-catenin through canonical Wnt signaling.…”
Section: How Receiving Stem Cells Perceive External Wnt Cuesmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, it has been suggested that b-catenin can interact with ES cell regulator Oct4 and in turn up-regulate Oct4 target genes ( Fig. 3E; Pardo et al 2010;van den Berg et al 2010). These interactions seem to be dependent on the stabilization of b-catenin through canonical Wnt signaling.…”
Section: How Receiving Stem Cells Perceive External Wnt Cuesmentioning
confidence: 97%
“…(D) Furthermore, it has also been proposed that Hipk2-mediated release of the TCF3 repressor can lead to the replacement of the TCF1 activator working with b-catenin for target gene activation (Hikasa and Sokol 2011;Yi et al 2011). (E) Another model proposed in ES cells is a TCF-independent regulation of b-catenin via interacting with ES cell core factor Oct4 to transactivate target genes (Pardo et al 2010;van den Berg et al 2010). These alternative models have been proposed to maintain the pluripotency of ES cells.…”
Section: How Receiving Stem Cells Perceive External Wnt Cuesmentioning
confidence: 99%
“…Oct4 cooperates with many other factors to establish pluripotency. In mouse ES cells, proteomic studies revealed that Oct4 binds to as many as 92 proteins (Wang et al, 2006;Pardo et al, 2010), which implies that intracellular context can have a significant impact on reprogramming. When fusing a somatic cell with an ESC, or transferring its nucleus into an oocyte (where many Oct4 binding partners are naturally present), endogenous pluripotency genes can be turned on in two days, much more rapidly than reprogramming with a few defined factors (Cowan et al, 2005;Egli et al, 2007).…”
Section: Molecular Mechanism Of Reprogramming To Pluripotency the Funmentioning
confidence: 99%
“…Recent proteomic screens, taking a more unbiased approach, have expanded these networks considerably by screening for proteins that directly interact with pluripotency factors. This has indicated that Oct4 (Pardo et al 2010;van den Berg et al 2010) and Nanog (Wang et al 2006), either directly or indirectly, interact with an extensive set of proteins, including transcription factors, chromatin remodelers, and components of the basal transcriptional machinery. Many of these interactions have been shown to be functional, indicating that the activity of both Oct4 and Nanog is modulated by a large number of cofactors (Wang et al 2006;Pardo et al 2010;van den Berg et al 2010).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%